Dynamic spectrum sharing for hybrid access in OFDMA-based cognitive femtocell networks - Deng, Qingyong; Li, Zhetao; Chen, Jiabei; Zeng, Fanzi; Wang, Hui Ming; Zhou, Liang; Choi, Young June (IEEE Transactions on Vehicular Technology, 2018)
Cognitive femtocell has emerged as one of the promising ways to solve the indoor coverage and spectrum shortage problems in cellular networks. However, it is a challenge to motivate both macro base station and femtocell access points FAPs to adopt this hybrid access policy. In this paper, we propose a systematic dynamic spectrum sharing framework for hybrid access in orthogonal frequency-division multiple-access-based cognitive macro-femtocell networks. In this framework, the MBS offloads some macro user equipments MUEs to FAP to improve the transmission performance and save energy. In return, the MBS leases a portion of its spectrum to FAP. Then, the FAP can use a part of spectrum for its own transmission and use another part to serve MUEs. We design an auction-based approach where each FAP receives additional MUE as bidders, while MBS acts as auctioneer. We formulate the dynamic resource sharing as a sum utility maximization problem. Numerical results demonstrate that both the macro and femtocell could get benefit from our framework.
Keywords: auction; Cognitive femtocell; Dynamic scheduling; Dynamic spectrum sharing; Femtocell Networks; Hybrid-access; Resource management; Ultra-fast; Vehicle dynamics; Auction; Cognitive femtocell; Dynamic spectrum sharing; Hybrid access